Burnout in competitive and elite athletes - Gustafsson, H. (Örebro Studies in Sport Sciences, 2007)
Intensified training regimes and increasing competitive pressure make some athletes leave sports with shattered hopes and dreams. A number of these athletes drop out of sports due to burnout, which is characterized by an enduring experience of emotional and physical exhaustion, reduced sense of accomplishment and devaluation of sport participation as a consequence of prolonged chronic stress. Loss of engagement and diminished motivation also characterize burnout. But burnout is more than just a simple stress reaction, as not all athletes who experience stress burn out. Study I investigates the prevalence of burnout among competitive athletes. The number of athletes showing high levels of burnout was found to be between 1 and 9%. The number of athletes suffering from severe burnout was estimated at 1-2%. Contrary to what has been speculated, burnout was not more common in individual sports than in team sports. Study II investigated the burnout process using a case-study approach. It was found that burnout can evolve with different levels of severity, time perspectives and characteristics. There appears to be a relationship between overtraining syndrome and burnout, and the study gave support to the notion that burnout is the most severe outcome on the training fatigue continuum. Early success might lead to high expectations and an inner pressure to train, which in the three cases made the athletes ignore signs of maladaptation. Performance-based self-esteem appears to be a "driving force" in the burnout process. In Study III the burnout experience was investigated using qualitative interviews. Lack of recovery, "too much sports" and high external demands were described as causes of burnout. A stressful situation with multiple demands from sport, school and social relationships leads to a total overload, which has both physiological and psychological consequences. Critical factors were a unidimensional identity, performance-based self-esteem, an inflexible organization and feelings of entrapment. These restraining factors made the athletes remain in sports despite negative outcomes. Thus the three studies indicate that burnout is a serious problem in competitive and elite sports, that restraining factors offer an explanation for why athletes remain in sport despite negative outcomes, and that striving for self-esteem is crucial in the development of burnout.